The Impact of Service Quality and Facilities On Passenger Satisfaction at Terminal 1 Departures Soekarno-Hatta International Airport - Aqsal Fahriz Ansari; Syahfa Putri Casavianca; Aisyah Rahmawati; Amrulloh Ibnu Kholdun (Jurnal Siber Multi Disiplin, 2026)
Service quality and airport facilities play an important role in passenger satisfaction, particularly at Terminal 1 Departures of Soekarno-Hatta Airport. This study aims to analyze the effect of service quality and facilities on passenger satisfaction at Terminal 1 Departures. Service quality factors include punctuality, terminal conditions, and process efficiency, while facility factors include accessibility, cleanliness, and the availability of supporting amenities. This research uses an accidental sampling technique with 349 respondents who were conveniently selected from passengers who have utilized services at Terminal 1 Departures of Soekarno-Hatta Airport. The data collected was analyzed using the linear regression method with SPSS to identify the relationship between variables and evaluate their effect on customer satisfaction. The results show a significant effect of service quality and facilities on passenger satisfaction at Terminal 1 of Soekarno-Hatta Airport, highlighting the importance of improving these elements to enhance the overall passenger experience.